PENDAMPINGAN DAN PEMBERDAYAAN IBU HAMIL UNTUK MENCEGAH BALITA STUNTING DI KELURAHAN SAMAAN KECAMATAN KLOJEN KOTA MALANG - Ibnu Fajar; Hasan Aroni; Juin hadisuyitno (Politeknik Kesehatan Kemenkes malang, 2021)
Malang City is one of the autonomous regions and is the second big city in East Java after Surabaya City. Malang City is currently listed as the city with the second smallest poverty percentage in East Java after Batu City, which is 5.9 percent of the total population. Nutritional problems in Malang City have been presented in the Basic Health Research of East Java Province in 2013. The incidence of stunting in Malang City has increased from 2007 to 2013 by 22.3 – 29.6%. In the context of preventing the occurrence of Stunting Toddlers, mentoring will be carried out with Cadres who have been trained in the first stage of Community Service for pregnant women who have a history of and or are at risk of giving birth to short - very short toddlers. Provide assistance to pregnant women in order to prevent stunting in toddlers in Samaan Village, Kec. Lowokwaru in Malang City. Community service is carried out by providing assistance by cadres to pregnant women for 6 months in Samaan Village, Rampal Celaket Community Health Center. The age of pregnant women in the Rampal Celaket Health Center area based on the results of the questionnaire was <20 years totaling 2 (28.5%) people, 21-25 years old 2 (28.5%) people, 26-30 years old totaling 1 (14.2% ) people, and >40 years old amounted to 1 (14.2%) people. all pregnant women are ordinary housewives and family income <UMR as many as 7 people (100%). Pregnant women before education showed that the 7 mothers involved had a low level of knowledge. Most of the pregnant women have consumption levels of energy, protein, fat, and carbohydrates which are included in the category of weight deficit (consumption rate <70%). A total of 57.1% (4 people) of pregnant women experienced Chronic Energy Deficiency (KEK). There was an increase in knowledge of pregnant women about MPGRS, Balanced Nutrition, Exclusive Breastfeeding for toddlers, the accuracy of giving MP ASI to toddlers, Clean and Healthy Life Behavior (PHBS).